Protective and therapeutic potentials of Trichinella spiralis larval antigen in murine induced colitis - Enas A. M. Huseein; Samia S. Alkhalil; Hanan S. M. Farghaly; Haiam M. M. Farrag; Hanaa Y. Bakir; Noha M. Aboulhagag; Samah S. M. Mohamed; Mona Gaber (Scientific Reports)
Abstract The intolerable side effects and clinical limitations of current conventional therapies for inflammatory bowel diseases (IBDs), there is a pressing need for alternative treatment options. Helminthes adapt immune responses of their hosts to reduce immune-mediated IBDs. The identification of the mechanism responsible for this beneficial effect on IBDs will provide another feasible approach to treating these diseases. The study was designed to investigate the possible protective and therapeutic role of Trichinella spiralis (T. spiralis) crude larval antigen extract in mice challenged with 2,4,6-trinitrobenzene sulfonic acid (TNBS) to induce colitis. Colitis was induced by intra-colonic instillation of TNBS (5 mg/ml in 50% ethanol), preceded or followed by intra-peritoneal (i.p.) administration of a single dose of T. spiralis crude larval antigen extract (100 µg/mouse). Colonic damage was assessed macroscopically and microscopically, and the expression of myeloperoxidase (MPO) was evaluated by immunohistochemistry. Colonic interleukin-10 (IL-10) and serum nitric oxide (NO) levels were also measured. Administration of T. spiralis crude larval antigen extract before induction of colitis reduced colitis severity as demonstrated by reduced colon weight-to-length ratio, improved macroscopic and microscopic scores, increased colonic IL-10 expression, and diminished colonic MPO protein expression. Moreover, there was a significant negative correlation between serum NO and colonic IL-10 levels. In addition, the preventive potential of T. spiralis crude larval antigen extract against TNBS-induced colitis was more prominent than its therapeutic effect. These findings support the hypothesis that T. spiralis has both prophylactic and therapeutic potential in inflammatory bowel diseases, which may be via an increase in IL-10 with predominance of its prophylactic role.